O sistema de classificação nominal Akwe-Xerente (Jê): âmbitos de análise - SIQUEIRA, Kênia Mara de Freitas (2010)
The need to describe and document the languages threatened with extinction has been gaining importance in the last decades, given the growing risks of cultural loss and the knowledge accumulated by indigenous people. The purpose of continuity of each one of these languages is ensured by actions based on the results of studies which focus on the description of the sociolinguistic problem, as well as on the description and analysis of the linguistic aspects which characterize the language of a determined linguistic family, since the death of a language means, among many other things, an undetermined loss of the science of Linguistics and, above all, the disrespect for the rights of these people to preserve their immaterial richness. The present research has as objective to answer some questions regarding the use of classifiers, terms of classes and names in classifying function as components of the classifying system of the language Akwe-Xerente (Jê), spoken by the indigenous people of the same name. The Akwe-Xerente add up to about 3,100 people and inhabit indigenous lands in the region of Tocantinia, in the Tocantins State. The description of the system of the Xerente classification is based on theoretical functional references for the recognition and differentiation of some nominal radicals which may occur in the function of classifying or organizing the classes which show common characteristics amongst the designated items such as form, size, aspect, consistence and function. This research is structured in the following way: In Chapter 1 are presented some proposals of elaboration of typology of sociolinguistics, to outline the contact situation in which the Xerente language is found nowadays; the chapter also gives a description of the methodology used to collect, select, and the process of systematization of the data. These procedures are constituted of a sequence of steps based on the methods of research for the Linguistic of field of synchronic base. In Chapter 2 an exposition is made of the theoretical views used in the description and analysis of the aspect of the nominal classifying system of the language. Chapter 3 shows the morphological criteria used in the definition and delimitation of the concepts of the words in the Xerente language, of the name, the compound name (compound word), and some characteristics of the name referring to the possibility of marking the possession/possessor in a certain group of Xerente names. In Chapter 4, the focus is in the description of aspects of nominal classifying in relation to the nominal stems which act as terms of classes and names in classifying function. This research is part of the LIBA Project Brazilian Indigenous Threatened Languages: Documentation (description and analysis and sociolinguistic typology) and means for offering subsidies in the linguistic range for the education program, as well as contributing in the scientific recognizance of related aspects to the classifying systems and linguistic category.